Muscle progenitor cells are required for skeletal muscle regeneration and prevention of adipogenesis after limb ischemia - Abbas, Hasan; Olivere, Lindsey A.; Padgett, Michael E.; Schmidt, Cameron A.; Gilmore, Brian F.; McCord, Timothy J.; Southerland, Kevin W.; McClung, Joseph M.; Kontos, Christopher D. (Frontiers in Cardiovascular Medicine, 2023)
Skeletal muscle injury in peripheral artery disease (PAD) has been attributed to vascular insufficiency, however evidence has demonstrated that muscle cell responses play a role in determining outcomes in limb ischemia. Here, we demonstrate that genetic ablation of Pax7+ muscle progenitor cells (MPCs) in a model of hindlimb ischemia (HLI) inhibited muscle regeneration following ischemic injury, despite a lack of morphological or physiological changes in resting muscle. Compared to control mice (Pax7WT), the ischemic limb of Pax7-deficient mice (Pax7delta) was unable to generate significant force 7 or 28 days after HLI. A significant increase in adipose was observed in the ischemic limb 28 days after HLI in Pax7delta mice, which replaced functional muscle. Adipogenesis in Pax7delta mice corresponded with a significant increase in PDGFRalpha+ fibro/adipogenic progenitors (FAPs). Inhibition of FAPs with batimastat decreased muscle adipose but increased fibrosis. In vitro, Pax7delta MPCs failed to form myotubes but displayed increased adipogenesis. Skeletal muscle from patients with critical limb threatening ischemia displayed increased adipose in more ischemic regions of muscle, which corresponded with fewer satellite cells. Collectively, these data demonstrate that Pax7+ MPCs are required for muscle regeneration after ischemia and suggest that muscle regeneration may be an important therapeutic target in PAD.